Assessment of area conservation in the Arab-Islamic city: the case of historic Cairo - Sedky, Ahmed Mohamed Ali (The University of Edinburgh, 2004)
Historic Cairo is a significant medieval urban phenomenon that has suffered uninterrupted deterioration since the mid nineteenth century. This led to questioning the quality of area conservation schemes in Cairo. Are they superficial, focusing only on restoration, which limits the focus of conservation only to the physical aspects of historic areas? Are they only designed to attract tourist dollars regardless of other social and local cultural considerations? Could the financial deficiency be the main reason for such a continuing environmental decline as proclaimed by the planners and officials in charge of safeguarding Historic Cairo?

All these questions besides many others inspired this investigation to explore the deficiencies and obstacles affecting area conservation in Historic Cairo. These questions are clustered into two main directions: the first focuses on the commission, i.e. the quality of executing area conservation schemes. The second searches for the reasons and goals for which the mission of a conservation scheme is pursued.

The commission inquiry defines what to conserve, the most significant values and qualities that give a meaning to the historic area to be safeguarded as addressed in Chapters One and Two. It also investigates how to conserve these areas without jeopardising such environmental values and qualities, as elaborated in Chapters Three and Four. On the other hand, the mission inquiry is probed through indepth analysis of policies and the political model responsible for them in Egypt, as elaborated in Chapter Six.

Since area conservation is still in its infancy in Historic Cairo, this research broadens its scope to investigate the Arab -Islamic Context. Through this broader context, many case studies were consulted along Chapters one to Four. These helped define comprehensive environmental assessment criteria, envisaged through a comprehensive sampling framework that incorporate all the active agents, based on integrating all the above environmental qualities, values and conservation and policy- making processes, as synthesised in Chapter Five.

Such a comprehensive assessment model is the actual contribution of this research to area conservation general literature, through which it was possible to explore one of the most chaotic urban phenomena, Historic Cairo, as conducted in Chapter Six. The implications of such an investigation identified that historic areas in Cairo are not envisaged as the last refuge of traditional culture and lifestyle but rather as a potential venue to attract foreign currency through development for cultural tourism. In addition, the continuing environmental deterioration pointed above, is mainly due to inter governmental organisational conflicts, which cripple the conservation and urban upgrading process in Egypt in general.